(untitled) (Cambridge, Mass., 1994)
Is capitalism everywhere driven by the same logic of market forces, contract, and individualistic motivation? Or is Japan different? These eighteen contributions by leading Japanese economists shed light on a number of issues in this increasingly important debate. The variety of perspectives and the range of firms covered -- not only the large industrial corporation but cooperatives, public enterprises, and mutual life insurance companies as well -- provide a broad overview that few other books on Japanese business can offer. In a new introduction to this English-language edition, Ronald Dore and Hugh Whittaker identify and summarize the salient themes and sharpen the points discussed.Chapters are grouped into five parts:- Part I identifies characteristics of the typical Japanese firm and the enterprise system.- Part II examines interfirm behavior such as trading, subcontracting, and cross-shareholding in enterprise groups.- Part III describes general firm behavior: how businesses invest in research, equipment, and product development.- Part IV takes a look at the employment system -- specifically, competition, deployment of human resources, and the traditional bonus system (a particularly significant feature of Japanese firms that differentiates them from their Western counterparts).- Finally, part V looks at specific kinds of firms: cooperatives, public utilities, and life insurance companies.
Keywords: Industrial management,Business enterprises,Quản lí công nghiệp,Doanh nghiệp kinh doanh; Japan,Japan,Nhật Bản,Nhật Bản